SPESIASI DAN BIOAVAILABILITAS LOGAM TEMBAGA (Cu) PADA BERBAGAI UKURAN PARTIKEL SEDIMEN DI KAWASAN PANTAI SANUR - Kristina Indra Yanthy T; Emmy Sahara; I G. A. Kunti Sri Panca Dewi (Jurnal Kimia (Journal of Chemistry), 2013)
A research on bioavailability and speciation of Cu in various sediment particle sizes collected from three sampling sites namely, Sanur, Sindhu and Mertasari Beaches along Sanur Beach was carried out. This study was aimed to determine the fractions of Cu available for aquatic organism and the geochemical forms of Cu in the sediments. Samples pretreatment were carried out by digestion with the use of the mixture of HNO3 and HCl (3:1). The bioavailability and speciation were accomplished by the appliation of  single exraction (with EDTA and HCl ) and sequential extraction techniques. Generally, it was found that EDTA extraction yielded higher bioavailability than that of HCl extraction. The highest bioavailability of Cu was showed by the sediment from Sanur Beach and Sindhu Beach at particle size of < 63 µm and from Mertasari Beach at particle size of 63-106 µm. From Cu speciation results it was found that the bioavailable (fractions of easily, freely, leachable, and exchangeable (EFLE), Fe/Mn oxide, organic and sulphide) and the resistant fractions were as follows: Sanur Beach at particle size of <63 µm were 8,28% and 10,31%, particle size of 63-106 µm were 5,34% and 9,13%, and particle size of >106 µm were 18,07% and 5,26%. Sindhu Beach at particle size of <63 µm were 17,32% and 15,69%, particle size of 63-106 µm were 6,98% and 9,92%, and particle size of >106 µm were 7,28% and 7,77%. Mertasari Beach at particle size of <63 µm 8,85% and 11,79%, particle size of 63-106 µm were 13,33% and 20,85%, and  particle size of  >106 µm were 17,99% and 38,42%.